MONITORING THE DEVELOPMENT OF URBAN HEAT ISLAND IN THE URBAN AREA OF YOGYAKARTA FROM 2013 TO 2023 - Ikhsan, Muhammad; Sunarharum, Tri Mulyani (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Cities function as centers of economic activity within a region and act as strong magnets for people who migrate and settle in urban areas, giving rise to the phenomenon of urbanization. Urbanization leads to an increase in the population of urban areas, including the Yogyakarta Urban Area. This process drives land-use changes and the expansion of built-up areas to accommodate housing needs and infrastructure development that supports population mobility. As a consequence of land-use changes and the growth of built-up areas, climate conditions are affected. The loss of vegetation, if not properly managed, results in rising temperatures known as the Urban Heat Island (UHI) phenomenon. The purpose of this study is to identify the changes in Urban Heat Island in the Yogyakarta Urban Area from 2013 to 2023. The research method used is quantitative deductive, involving spatial, statistical, and descriptive analysis techniques. This study applies NDVI (Normalized Difference Vegetation Index) and LST (Land Surface Temperature) analysis, with the final output being the UHI index. The findings show a significant increase in the UHI index, particularly in the northern part of the Yogyakarta Urban Area. The subdistricts experiencing the highest increase in UHI include Godean, Gamping, Mlati, Ngaglik, Depok, and Ngemplak.